‘FORKLIFT TO GRID’ – HOW TO SYNERGISE THE ELECTRICITY AND LOGISTICS SECTORS - Knez, Matjaž; Predin , Andrej Predin; Rosi , Bojan (Journal of Energy Technology, 2024)
Interruptions of electricity supply at the national level are due to a lack of production capacity as well as a lack of transmission capacity, and have an immediate and significant impact on industry, households and other sectors. It is therefore necessary to constantly seek new ways of storing electrical energy and thus have a positive effect on the coverage of energy and peak power system stabilization. This paper deals with the possibility of the integration of environmentally friendly renewable energy sources with modern technologies into the energy management of logistics processes, which is very important in global business and helps to increase both the efficiency and effectiveness of business systems. This paper shows the study of the current research findings on the ‘Vehicle to Grid’ innovative concept and a proposed theoretical model of F2G integration into energy management of a warehouse. Analyses of data, calculations of the economic value and of the profitability of the proposed business model yielded positive results that fully confirm the thesis that the integration of environmentally friendly renewable energy sources and new technologies into the logistic processes can improve logistics management while minimizing the negative impact of business on the environment.